The Concept of Tazkiyat al-Nafs by Al-Ghazali as a Method in Moral Education - Erlin Wulandari; Evi Verlantika; M Hafidz Khusnadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Humans are sacred creatures who are equipped with the perfection of reason and soul because with reason and soul humans can understand themselves correctly. The existence of mental illness, will have an impact on human behavior patterns (morals). It can be said that this mental illness has an impact on the formation of despicable morals that plague human life. Departing from this background, the author takes the title The Concept of Tazkiyat al-Nafs Al- Ghazali as a Method in Moral Education. The research that the author conducted is included in the descriptive qualitative research of critical analysis. In collecting data, the author uses the documentation method, namely by collecting various books and journals. As for data analysis, the author uses content analysis techniques. The explanation of tazkiyat al-nafs with the description that the soul is likened to a glass whose perfection lies in its ability to accept the image in front of it. Likewise with the soul, if the soul is mixed with disease then the steps taken is to clean the soul with a variety of positive things, so that the soul is clean again. The methods used by the concept of tazkiyat al-nafs include mujahadah and riyadhah methods, exemplary methods, habituation methods, story methods and advice methods. While the implementation of the concept of Tazkiyat al-Nafs Al- Ghazali in moral education by using several means, namely Tauhid, Sholat, Zakat and Infaq, Fasting, Reading the Quran, Meditating, Remembering death, Mushabah and Muqorobah Zuhud and Taubat.